The sIgA and histatin-5 expressions in saliva of early childhood caries and caries-free children based on period times - Dharli Syafriza; Heriandi Sutadi; Ameta Primasari; Yahwardiyah Siregar (Journal of Syiah Kuala Dentistry Society, 2020)
To analyze the level of sIgA and Histatin-5 expression in Early Childhood Caries (ECC) and caries-free children. Saliva was collected from 31 subjects of ECC and 29 caries-free (ages 9-32 months). The level expression of sIgA and Histatin 5 was analyzed by enzyme-linked immunosorbent assay. The distribution and frequency of subjects consist of boys 47% and girls 53% with the average of ages 1-12 month 21% and 13-24 month 79%.sIgA and Histatin 5 expressions differ from the month periods tested (1, 3, and 9 months) but do not show any significant difference from each examination period (1 with three months; p0.05: 0.116), (1 with nine months; p 0.05: 0.766), and (3 to 9 months; p0.05: 0.398). The expression of sIgA and Histatin 5 of boys and girls were not significant (p0.05:0.550) and weak correlation (r = 0.079).The level expression of sIgA in the Caries-free higher than ECC (p0.05). Whereas the expression of Histatin 5 in ECC higher than Caries-free (p0.05). The sIgA correlating in ECC and caries-free is significant (p0.05) and no correlation (r =- 0,29). Whereas Histatin 5 in the ECC and caries-free were strong correlation = 0,84. Both the result of ECC and caries-free suggested that the antibodies have been involved in the caries pathogenesis. In the ECC cases that occurred to decrease sIgA levels and increased of Histatin 5 levels, both antibodies have expressed in Caries-free Children. Both sIgA and Histatin 5 involved in the pathogenesis caries infection in children.KEYWORDS: Antibodies; Early Childhood Caries; saliva; secretory immunoglobulin A; Histatin-5